Miniature Inverted Repeat Transposable Element Insertions Provide a Source of Intron Length Polymorphism Markers in the Carrot (Daucus carota L.) - Stelmach, Katarzyna; Macko-Podgórni, Alicja; Machaj, Gabriela; Grzebelus, Dariusz (Frontiers in Plant Science, 2017)
The prevalence of non-autonomous class II transposable elements (TEs) in plant genomes may serve as a tool for relatively rapid and low-cost development of gene-associated molecular markers. Miniature inverted-repeat transposable element (MITE) copies inserted within introns can be exploited as potential intron length polymorphism (ILP) markers. ILPs can be detected by PCR with primers anchored in exon sequences flanking the target introns. Here, we designed primers for 209 DcSto (Daucus carota Stowaway-like) MITE insertion sites within introns along the carrot genome and validated them as candidate ILP markers in order to develop a panel for genotyping the carrot. As a proof of concept, 90 biallelic DcS-ILP markers were selected and used to assess genetic diversity of 27 accessions comprising wild Daucus carota and cultivated carrot of different root shape. The number of effective alleles was 1.56, mean polymorphism informative content was 0.27, while the average observed and expected heterozygosity was 0.24 and 0.34, respectively. Sixty seven loci showed positive values of Wright’s fixation index. Using Bayesian approach, two clusters comprising four wild and twenty three cultivated accessions, respectively, were distinguished. Within the cultivated carrot gene pool, four subclusters representing accessions from Chantenay, Danvers, Imperator, and Paris Market types were revealed. It is the first molecular evidence for root-type associated diversity structure in the western cultivated carrot. DcS-ILPs detected substantial genetic diversity among the studied accessions and, showing considerable discrimination power, may be exploited as a tool for germplasm characterization and analysis of genome relationships. The developed set of DcS-ILP markers is an easily accessible molecular marker genotyping system based on TE insertion polymorphism.